Design and Optimization of a Small-Scale Horizontal Axis Wind Turbine Blade for Energy Harvesting at Low Wind Profile Areas - Umar D.A.; Yaw C.T.; Koh S.P.; Tiong S.K.; Alkahtani A.A.; Yusaf T. (MDPI, 2023)
Airfoils; Angle of attack; Energy harvesting; Iterative methods; Kinetic energy; Kinetics; MATLAB; Reynolds number; Speed; Turbine components; Wind; Wind power; Wind turbines; Blade design; Low wind speed; Low winds; National advisory committee for aeronautics; Power harvesting; Q-blade; Rotor blades; Small wind turbine; Tip speed ratio; Wind profiles; Turbomachine blades